Recombination of oxidized samples of DHA and purified sunflower oil reproduces the odor profile of impaired algae oil from Schizochytrium sp. and reveals the odor contribution of fatty acids other than DHA. (15th April 2022) - Wen, Yun-Qi; Xue, Chang-Hu; Zhang, Hong-Wei; Xu, Li-Li; Wang, Xiao-Han; Bi, Shi-Jie; Xue, Qian-Qian; Xue, Yong; Li, Zhao-Jie; Velasco, Joaquín; Jiang, Xiao-Ming
Abstract: Algae oil from Schizochytrium sp. is one of the major natural sources of ω-3 polyunsaturated fatty acids (PUFAs), but its applications in foods are limited because of its unpleasant odor. The complex composition of algae oil originates an odor profile that differs from that of its major PUFA, i.e. docosahexaenoic acid (DHA). The aim of this work was to explore the specific role of DHA oxidation in the odor profile of algae oil. According to the fatty acid composition and odor characteristics, oxidized sunflower oil was selected and combined with oxidized DHA to simulate the odor profile of algae oil. The recombination oil showed similar odor characteristics to the algae oil sample indicating that DHA oxidation was key in the formation of the unpleasant odor in algae oil and that oxidation of fatty acids other than DHA also made a contribution. The constructed off-flavor of algae oil was a consequence of a synthetic effect between odorants from oxidized DHA and oxidized oleic, linoleic and linolenic acid. This study provided a reference for the source research of volatile substances producing fishy odor in algae oil. Highlights: DHA alone was not able to form the characteristic off-flavor of algae oil. Algae oil odor was reproduced combining oxidized samples of DHA and sunflower oil. DHA oxidation was key in the formation of the unpleasant odor in algae oil. Oxidation of oleic, linoleic and linolenic also contributed to algae oil off-flavor. A synthetic effect of odorants was involved in the reproduction of off-flavor.